2011
DOI: 10.1210/jc.2011-0446
|View full text |Cite
|
Sign up to set email alerts
|

The Role of β-Cell Function and Insulin Sensitivity in the Remission of Type 2 Diabetes after Gastric Bypass Surgery

Abstract: In morbid obesity, Roux-en-Y gastric bypass causes rapid and profound metabolic adaptations; insulin sensitivity improves in proportion to the weight loss, and β-cell glucose sensitivity increases independently of weight loss. Over a period of 1 yr after surgery, diabetes remission depends on the starting degree of β-cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 37 publications
11
102
2
3
Order By: Relevance
“…It is assumed that the elevated C-peptide levels in morbidly obese diabetic patients implicate well-preserved pancreatic β cell function capable enough to compensate for the increased insulin resistance. Nannipieri et al suggested that on a background of better β cell function, improvement in β cell glucose sensitivity after RYGB represents the major determinant in type 2 diabetes remission [30]. In the similar sense, younger age and no insulin requirement, which are known to indirectly reflect better β cell function, also served as predictors of diabetes remission in the present study, although the significance varied across the different types of analyses.…”
Section: Discussionmentioning
confidence: 45%
“…It is assumed that the elevated C-peptide levels in morbidly obese diabetic patients implicate well-preserved pancreatic β cell function capable enough to compensate for the increased insulin resistance. Nannipieri et al suggested that on a background of better β cell function, improvement in β cell glucose sensitivity after RYGB represents the major determinant in type 2 diabetes remission [30]. In the similar sense, younger age and no insulin requirement, which are known to indirectly reflect better β cell function, also served as predictors of diabetes remission in the present study, although the significance varied across the different types of analyses.…”
Section: Discussionmentioning
confidence: 45%
“…During the 12 months after RYGB, the likelihood and extent of diabetes remission is dependent on the degree of preoperative β-cell dysfunction. 91 In large clinical studies, the eventual degree of weight loss generally correlated with the extent of metabolic benefit derived from surgery. EWL paralleled the magnitude of biochemical responses in studies by Schauer et al 92 …”
Section: Metabolic Changes With Bariatric Surgerymentioning
confidence: 99%
“…It is clear that the risk of developing T2D increases with an increase in BMI, but the severity of T2D in patients with a low BMI seems to implicate a deficiency in insulin secretion rather than a phenomenon of insulin resistance [22,25,27,35]. The duration of diabetes would confirm this hypothesis, with a better (reserve) for insulin secretion in obese patients recently affected by T2D [3,10,[21][22][23][24][25][26][27]30].…”
Section: Discussionmentioning
confidence: 97%